2020
DOI: 10.12688/f1000research.27145.1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term health effects of antipyretic drug use in the ageing population: protocol for a systematic review

Abstract: Background: Fever is suppressed with drugs due to discomfort and risk of organ damage. However, there is some compelling evidence for the benefits of fever. The elderly are a special population in this regard as they have a blunted fever response. The benefit-harm balance of antipyretic use in this population is unclear.   This study aims to provide the synthesized best evidence regarding long-term health effects of antipyretic treatment in the elderly during infections, investigating the onset/worsening of co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…26,27 Studies have hitherto shown that the presence of fever may be associated with better outcomes during infection although the evidence is still lacking in certainty. 25,28,29 In our database, the presence of fever was indeed associated with better prognosis (Table 2). However, the temperature range did not influence the clinical outcome in the cases presented here (Table 4).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…26,27 Studies have hitherto shown that the presence of fever may be associated with better outcomes during infection although the evidence is still lacking in certainty. 25,28,29 In our database, the presence of fever was indeed associated with better prognosis (Table 2). However, the temperature range did not influence the clinical outcome in the cases presented here (Table 4).…”
Section: Discussionmentioning
confidence: 71%
“…In the absence of fever, cough, and a clinical/laboratory image of pneumonia (without fever) were seen to dominate. Fever was of special interest as fever is conventionally suppressed during infections, 25 whereas homeopathy promotes a high fever during infection as a part of the efficient acute inflammatory response. 26,27 Studies have hitherto shown that the presence of fever may be associated with better outcomes during infection although the evidence is still lacking in certainty.…”
Section: Discussionmentioning
confidence: 99%
“…Fever is of special interest, as fever is conventionally suppressed during infections [25], whereas homeopathy promotes a high fever during infection as a part of the efficient acute inflammatory response [26,27]. Studies have hitherto shown that the presence of fever may be associated with better outcomes during infection, although the evidence is still lacking in certainty [25,28,29]. In our database, the presence of fever was indeed associated with better prognosis (Table 3).…”
Section: Discussionmentioning
confidence: 74%
“…In the absence of fever, cough and a clinical/laboratory image of pneumonia (without fever) were seen to dominate. Fever is of special interest, as fever is conventionally suppressed during infections [25], whereas homeopathy promotes a high fever during infection as a part of the efficient acute inflammatory response [26,27]. Studies have hitherto shown that the presence of fever may be associated with better outcomes during infection, although the evidence is still lacking in certainty [25,28,29].…”
Section: Discussionmentioning
confidence: 99%